Organized Chronic Subdural Hematoma Following Ventriculoperitoneal Shunt: A Case Report - Shrestha, Ram Kumar; Sharma, Mohan Raj; Sedain, Gopal (Nepal Journal of Neuroscience, 2016)
Subdural Hematoma (SDH) or effusion following Ventriculoperitoneal (VP) shunt for hydrocephalous is not an unusual complication. However, we rarely come across organized chronic subdural hematoma (CSDH) following shunts. We present a case of organized CSDH in a four-year-old female child who presented with seizure three and half year after the VP Shunt placement for obstructive hydrocephalus due to aqueductal stenosis. The child was managed with craniotomy and evacuation of hematoma with membranectomy. We report this unusual case and review the relevent literature.Nepal Journal of Neuroscience 12:46-48, 2015